The effect of seashells as filler in epoxy composites / Nor Azwin Ahad, Kwan Suk Lum and Khairulnisa Halim - Ahad, Nor Azwin; Kwan, Suk Lum; Halim, Khairulnisa (Faculty of Applied Sciences, 2023)
The presence of seashell wastes is generalized in seashores. Sometimes, these wastes must be removed to provide clean beaches and obtain quality signs. It is possible to use these wastes as bio-filler for polymer matrices. Therefore, the primary purpose of this research is to study the mechanical properties and oil absorption of various seashells, namely, clams, cockles, and mussels. These three types of seashells are used as filler in an epoxy matrix. The performance of the seashells was investigated at 10wt%, 20wt%, and 30wt%. Calcium carbonate (CaCO3) is the main constituent of seashells and one of the most commonly used inorganic fillers in the polymer industry. Cockle has the highest amount of CaCO3, followed by clam and mussel. The results disclose that adding the seashells as filler can improve tensile strength if the optimum filler loading is not exceeded. 10wt% of cockles in epoxy composites is reported as the best composition to achieve the highest tensile strength. Mussels and cockles absorb more oil in the epoxy composites at their various weight percentages. Besides, all seashells showed the highest oil uptake at 10wt% filler loading. Lower filler loadings lead to the absorption of more oil by the composites.